MRI and clinical characteristics of suspected cerebrovascular accident in nine cats. Issue 8 (August 2018) - Whittaker, Danielle E; Drees, Randi; Beltran, Elsa
Objectives: Cerebrovascular accidents (CVAs) are infrequently reported in cats. To date, clinical characteristics, including lesion localisation and MRI findings, have only been reported in two cats. The aim of the current study is to document MRI findings in cats presenting with CVAs over an 11 year period. Cases were reviewed according to initial clinical presentation, subsequent physical and neurological findings, predisposing systemic disease and short- and long-term (when available) outcome with a view to identifying any typical pattern in disease occurrence. Methods: Patient records of cats presenting to a single referral centre from January 2005 to September 2016 with acute onset, non-progressive (after 24 h) intracranial signs compatible with a CVA and where an MRI was performed within 72 h were retrospectively reviewed. Results: Nine cats met the inclusion criteria. All cats had ischaemic CVAs (presumptively diagnosed in eight cats and confirmed in one cat following post-mortem examination). No cases of haemorrhagic CVAs were identified. Four cats presented with territorial infarcts that were confined to the territory of the rostral or caudal cerebellar arteries (n = 4). Lacunar infarcts were identified in five cats in the location of the cerebrum (n = 1), the thalamus/midbrain (n = 2) and the medulla oblongata (n = 2). Concurrent systemic disease was identified in most (n = 8/9). In the present study short-term prognosis was favourable and 8/9 cats survived to 48 h following admission. Conclusions and relevance: CVAs in cats occur in the same vascular territories as in dogs and have similar MRI features. This study notes that the presenting cats had a high likelihood of concurrent disease (8/9 cases) but had a favourable short-term prognosis, if neither the clinical presentation nor concurrent disease were severe.